Unveiling the Complexity of PCOD: Exploring Contemporary Research and Scientific Breakthroughs Review - Kumar, N. Udaya (Asian Journal of Pharmaceutics (AJP), 2023)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder that significantly impacts reproductiveaged individuals globally. This paper explores recent breakthroughs in PCOS research that have revolutionized our understanding of its multifaceted nature. It delves into advancements in the understanding of etiology and pathophysiology through genetic research that has illuminated the genetic underpinnings of PCOS susceptibility. Insights into the intricate interplay of hormonal imbalances within PCOS and dysregulations in sex hormones, insulin, and other signaling molecules that contribute to PCOS symptomatology are discussed. A detailed examination of research into insulin resistance unveils its intricate connections with PCOS development, providing novel insights. The review emphasizes the role of personalized diagnostic and treatment approaches in harmonizing current research findings. It advocates for tailored strategies that consider each patient’s distinct presentation in recognition of PCOS heterogeneity. Ultimately, through a comprehensive assessment of contemporary PCOS research, this paper serves as a guiding light for clinicians and researchers and underscores the need for collaborative, evolving research to deliver targeted therapies.